Penggunaan Penilaian Kinerja untuk Mendukung Pembelajaran Daring di Perguruan Tinggi selama Pandemi Covid-19 - Delthawati Isti Ratnaningtyas; Rahma Nasir; Magfirah; Yulia Windarsih (Universitas Tadulako, 2021)
Online learning in higher education during the Covid-19 pandemic needs an alternative assessment that can measure students’ skills appropriately. The students tend to be assessed only by using formative and summative assessments. Assessment in online learning should consider students’ performances. Literature studies were conducted to collect relevant articles in journals and books to answer how to implement the performance assessment in online learning during the Covid-19 pandemic. The results showed that using the performance assessment can assess student skills in online learning during the Covid-19 pandemic. The performance assessment that is suitable to be implemented by using oral presentation, practical work, project investigation, group discussion, and portfolio in online learning. The performance assessment can measure content knowledge as well as incorporate higher-order thinking, scientific process, communication, and collaboration.